bGH/AluI and CSN3/HinfI Gene Polymorphisms in Holstein Cattle - Topal, Mehmet; Sözmez, Zeynep; Özdemi̇r, Memiş (Asian Educational Journal Publishing Group, 2018)
The aim of the study was to determine the gene and genotype frequencies of the bGH/AluI and CSN3/HinfI gene in the animal material obtained from organic farm by PCR-RFLP method. A total of 248 cattle of Holstein breed were genotyped for the bGH/AluI and CSN3 HinfI polymorphism. In bGH gene region, the LL, LV and VV genotype frequencies were 0.50, 0.48 and 0.02 respectively and In CSN3 gene region, the AA, AB and BB genotype frequencies were 0.71, 0.23 and 0.06 respectively. Both bGH/AluI and CSN3/HinfI genotypes were not found to be in equilibrium within the breed. Also, both heterozygosity were found at a high rate as 0.478 and 0.234 and the calculated FIS values were -0.24 and 0.20 respectively.
Keywords: 2. Zero hunger; 10. No inequality; 3. Good health